1999
DOI: 10.1046/j.1365-3059.1999.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and moisture on disease and fruit body development of Mycosphaerella pinodes on pea (Pisum sativum)

Abstract: The effects of temperature (5-30ЊC) and the duration of moisture on the development of ascochyta blight (Mycosphaerella pinodes) on pea seedlings, grown under controlled conditions, were investigated. The optimum temperature for monocyclic processes was 20ЊC. At this temperature, pycnidiospores germinated after 2 h, appressoria formed after 6 h and the germ-tube penetrated the leaf cuticle after 8 h. Disease symptoms were evident after 1 day of incubation and the first pycnidia formed after 3 days. Longer wett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 23 publications
6
44
0
Order By: Relevance
“…The extent and severity of disease depend on the cropping system and weather conditions. The most favorable conditions for the pathogen are frequent rainfall, high relative humidity, and leaf wetness duration (44,50). Pea plants may suffer frost damage during the winter, which can enhance ascospore germination and spore penetration into healthy tissue for M. pinodes (5,24,25).…”
mentioning
confidence: 99%
“…The extent and severity of disease depend on the cropping system and weather conditions. The most favorable conditions for the pathogen are frequent rainfall, high relative humidity, and leaf wetness duration (44,50). Pea plants may suffer frost damage during the winter, which can enhance ascospore germination and spore penetration into healthy tissue for M. pinodes (5,24,25).…”
mentioning
confidence: 99%
“…2). Ac cord ing to Roger et al (1999) tem per a ture over 20°C de creased de vel op ment of M. pinodes, while the dis ease was able to develop within a few days un der fa vor able mois ture and over a wide range of tem per a tures (15-25°C). On the other hand such weather in creased abil ity of seeds for ger mi na tion.…”
Section: Discussionmentioning
confidence: 94%
“…et Blox.) Petrak) anamorph Ascochyta pinodes L. K. Jones, Ascochyta pisi Libert and Phoma pinodella (L.K.Jones) Mor gan-Jones et Burch, is a se ri ous dis ease of Pisum sativum L., es pe cially in wet sea sons, of many coun tries over the world, like Can ada (Wallen 1974, Xue et al 1997, Aus tra lia (Bretag et al 1995), France (Roger et al 1999), Po land (Marcinkowska 2002). The plants may be infected dur ing all de vel op ment stages (Law yer 1984, Marcinkowska 1996b, Xue and Warkentin 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Under field conditions in France, pycnidia began forming 11 d after inoculation at flowering and at shorter intervals as the plants aged. Under controlled conditions, Roger et al (1999b) found that development of pycnidia was much more rapid and prolific and much less temperature-dependent where leaf surfaces were wet, compared with leaves under continuously high relative humidity. The relatively short latent period of M. pinodes allows multiple generations to develop under normal growing conditions in western Canada, so that inoculum pressure can become quite high by mid-to late July.…”
Section: Seed Yieldmentioning
confidence: 99%